O dveh verzijah romana S poti - Ogrin, Matija (Slavistična revija, 2008)
Izidor Cankar published the novel S poti twice (1913, 1919). The existence of the two somewhat different versions has no provoked any thoughts about their inner variation and about the implications that this could have for understanding of author's ideological and aesthetic views. A detailed comparision of the two versions reveals some interesting differences that are not without significance for the interpretation of the text, and indicates how the given circumstances dictated the choice of the concept of textual criticism in the scholarly edition of the novel S poti.
Keywords: besediloslovje; Cankar, Izidor, 1886-1958; Cankar, Izidor: S poti; literarne študije; Slovene literature; slovenska književnost; Text linguistics